Pemodelan Prediksi Nilai IQ Menggunakan Algoritma Machine Learning - Ramadhani, M. Akbar Tri; Permata Sari, Dewi; Sabilah, Anisa Aulia; Tabitha, Aghnia Hafsa; Rochmah, Ainur; Saputra, Andika; Natasya, Erin; Pratamah, Destra Andika (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
IQ stands for Intelligence Quotient. It is a numerical score obtained from various psychometric tests designed to measure a person's general intelligence or cognitive ability. IQ is often used as an indicator of academic potential, success in the workplace, and adaptability to new environments. However, it is important to remember that IQ is only one aspect of human intelligence. IQ assessments are widely used in fields as diverse as education, psychology, and employment. Manually administered IQ tests are often time-consuming, require human intervention, and are prone to error. On the other hand, the development of data-driven technology allows for faster and more accurate information processing. Machine learning is a system that can learn to make its own decisions without being reprogrammed by humans, allowing computers to become smarter and learn from their experience with data. That's why the author conducted research to develop an IQ prediction model using machine learning algorithms.